Pengaruh Implementasi Prosedur Pelayanan Kesehatan dan Sistem New Normal Terhadap Karyawan di PT. X - Vincent Christian; I Nyoman Sutapa (Jurnal Titra, 2023)
Company PT. X still implemented a work from office (WFO) work system during the Covid-19 pandemic, which made employees anxious and afraid when working. Therefore the company establishes policies and runs programs related to the control and prevention of Covid-19. Rules made and implemented by companies during the Covid-19 pandemic associated with the handling and preventing of the Covid-19 virus will continue until the post-Covid-19 period. The purpose of this study is to see whether the rules made by companies to increase employee engagement are still relevant to the post-Covid-19 pandemic situation. The research was conducted using the Structural Equation Modeling Method and with the help of SmartPLS software. Based on the results of the research that has been done, occupational safety and health have a significant effect on employee engagement. In contrast, terms have a substantial effect on burnout, and burnout significantly affects employee engagement. In conclusion, the company's program is quite effective and impacts employee engagement.